Synthesis of calcium oxide nanoparticles via carbon nanotubes template - Tengku Muhammad Amirul Tengku Izat Azmir, 1993- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2015)
Project Paper (Sarjana Muda Sains (Kimia)) - Universiti Teknologi Malaysia, 2015